Phenomenological Experiences of Grief Among Elderly Following Family Loss in Indonesia: A Roy’s Adaptation Model–Based Inquiry - Maulidina, Nur Hasanah; Hidayat, Syaifurrahman; Huzaimah, Nailiy; Salat, Sri Yunita Suraida; Andrian, Maulana Widi (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: The loss of a family member presents a deeply emotional challenge for older adults, often disrupting their physical, psychological, and social equilibrium. Elderly individuals experiencing grief commonly face intense sorrow, isolation, and alterations in their daily routines. Without effective coping mechanisms, these emotional responses may negatively impact their bodily functions and social relationships. This study aimed to explore the grief experiences of elderly individuals in coping with family loss using the Roy Adaptation Model as a guiding framework. Methods: A qualitative phenomenological design was employed, underpinned by the Roy Adaptation Model. Participants were selected through purposive sampling, with inclusion criteria consisting of elderly individuals aged 60 or above who had lost a nuclear family member within the past 6 to 12 months. Exclusion criteria included the presence of cognitive, sensory, or severe physical impairments. The study involved seven elderly participants, two family members, and one healthcare provider from Kalianget District in 2025. Data were collected via in-depth interviews and analyzed thematically through open, axial, and selective coding. Data saturation was confirmed after the seventh participant. The research adhered to COREQ reporting standards and received ethical clearance from the Health Research Ethics Committee of Wiraraja University (No: 1234/EC/2025) Result: Participants experienced grief through crying, withdrawal, and denial. Coping strategies included engaging in religious practices, sharing stories, and staying occupied. Four central themes emerged: grief experience, coping mechanisms, physiological changes, and interdependence Conclusion: Grief significantly affects the emotional, physical, and social well-being of the elderly. Support from families, healthcare professionals, and communities is vital to promote adaptive coping.